Effects of social isolation on locus coeruleus opioid receptor expression and affective behavior - John Tkaczynski; Jordan Riser; Maya Patel; Nicole Shellenbarger; Jin Park; Daniel Manvich; Daniel J. Chandler (Neurobiology of Stress)
Social isolation is a stressor that impairs homeostatic neuroendocrine functions and is associated with the development of several mood disorders characterized by persistent negative affect. Persistent feelings of loneliness have been growing public health concerns for several years and were greatly exacerbated by the onset of the COVID-19 pandemic. The problem has grown so severe the U.S. Surgeon General recently declared loneliness to be an epidemic health concern that is associated with poor mental and somatic health outcomes. Therefore, identifying mechanisms of neuroadaptation that contribute to the development of persistent negative affect is a critical step in the identifying better treatments for mood disorders. One region of the brain that becomes dysregulated in neuropsychiatric disease is the locus coeruleus. It is innervated by multiple stress-related peptidergic afferents, including those that release endogenous opioids to affect behavior. It is a major contributor to the behavioral limb of the stress response, but its role in the neurobiology of social behavior is understudied. Here we show that in laboratory rats, six weeks of social isolation leads to increased neophobia, reduced sociality, and passive stress coping. These behavioral changes are also associated with downregulation of the δ-opioid receptor and upregulation of the κ-opioid receptor in locus coeruleus. These findings suggest that extended social isolation promotes dysregulation of several opioid receptor subtypes in a brain structure that has an important role in regulating affective behavior, implicating them as potential targets for the treatment of neuropsychiatric disease associated with social isolation and loneliness.